3-D direct printing of silicone meniscus using a novel heat-curing extrusion based silicone printer - Luis Adiwati, Guntur Eric (Nanyang Technological University, 2019)
Silicone implants have been widely used as treatment for osteoarthritis of the knee with meniscal pathologies. Silicone products have conventionally been manufactured by direct or indirect molding methods which are expensive and time-consuming. The geometrical precision and aesthetic parameters of the end-products are also highly operator-dependent. Silicone 3D printing provides immediate benefits of customization, time and cost savings for patients. Typical non-printable meniscal substitutes lack the customizability of 3D printable implants and are mechanically weak for instantaneous weight bearing. Currently, 3D printed scaffolds, using hydrogels, suffer from the common major drawbacks of being mechanically weak and patients are unable to execute immediate post-surgical weight-bearing, ambulation and rehabilitation. To solve this problem, a 3D silicone meniscus implant which is 1) biocompatible, 2) mechanically similar to native meniscus and resistant to cyclic loading, and 3) directly 3D printable, has been developed. The main objectives of this research are: 1)To design, manufacture and optimize a novel extrusion-based 3D silicone printer with unique heating processes. The optimization of various printing parameters and printing processes will be studied by conducting design of experiments (DOE). This silicone printer will be able to perform Liquid Additive Manufacturing with different ranges of medical and non-medical grade silicones. 2) To 3D print a customized meniscus which has comparable biomechanical properties as those of the native meniscus. In a future design to the 3D printed meniscus, micro-channels and reservoirs will be incorporated into the meniscus to provide slow release mechanism for drugs, lubricants and growth factors. 3) To incorporate shape memory properties into currently commercially available liquid silicone rubber. This work reports the first demonstration of direct extrusion of heat-cured silicone using a two-part Ecoflex silicone rubber. The results provide a better understanding on the fabrication and workings of a heat-cured extrusion-based printer in the direct 3D printing of a silicone meniscus. For subsequent experimental purposes, Ecoflex silicone rubbers are used for their costs and biocompatibility. Their rheological, mechanical and biological properties are first characterized and these form the basis for the design and fabrication of the silicone printer. All hardwares and softwares used are open-sourced materials. The printer developed contains a pre-mixing station to ensure homogenous mixing of silicone prior to dispensing. The printing volume is demonstrated with the printing of an 8 cm3 cube. Secondly, printer parameters such as print velocities, nozzle diameters, nozzle-platform distance, flow-rates, nozzle temperatures and bed temperatures were selected for characterization and testing. The optimal processing window was established for each parameter. Overall, it was found that nozzle diameter and bed temperature were the major determinants on the accuracy and precision of printed dimensions in the x-y horizontal planes, while the bed temperature was the only significant determinant on construct. Thirdly, the optimization of the selected printing parameters was performed through regression analysis using design of experiments (DOE) and analysis of variance (ANOVA) methods. Nozzle diameters, nozzle temperatures and bed temperatures were the critical parameters which determined the print quality of silicone samples. The resolution of printing was characterized using basic and complex shapes, ranging from struts, cylinders, T-bones, cubes, polyhedron and finally meniscus. Overall, the result shows that the dimensions of the printed structures were close to the design dimensions. Fourthly, the printed silicone meniscus was compared with their molded counterparts through physical characterization (X Ray-CT, surface-profilometry, light-microscope, scanning electron microscopy, PBS absorption test), chemical characterization (FTIR, TGA/DSC, XRFS), mechanical characterization (compression tests, tensile, cyclic compression tests, failure tests) and biocompatibility characterization (proliferative and cell-viability assays). Results indicate that the silicone 3D Printing process does not alter the overall physical, biochemical, mechanical or biocompatible properties of the silicone meniscus implant printouts. Both the chemical and thermal stabilities of Ecoflex silicone rubber were demonstrated by FTIR and TGA/DSC, respectively. At all strain rates, Eco50 silicone meniscus implants and standard samples consistently showed higher stiffness and high modulus when compared to their Eco30 counterparts. Finally, cytotoxicity tests showed that both Eco30 and Eco50 silicone implants are safe for fibroblasts. Finally, the prospects and challenges of this 3D Printed meniscus are explored. Challenges arising from MRI DICOM file conversion to CAD STL format, in particular during segmentation, are discussed. Further potential of 3D printed meniscus was explored in 2 designs, namely drug-delivery reservoir channel and shape memory. A safe way of incorporating micro-channels and reservoir using mixed molten sugar-honey sacrificial mold is also discussed. The proof-of-concept of shape-memory property incorporation using TPU, into the silicone meniscus is also demonstrated.